Diseño de un modelo de tráfico a través de series de tiempo para pronosticar trafico Wimax - Salcedo Parra, Octavio José; Hernández Suárez, César Augusto; Escobar Díaz, Andrés (Ingeniería, 2006)
This paper tries to initiate to the reader in statistical models with time series, that allow to consider future forecasting of traffic in the modern Communication networks, making use of the forecasting of the traffic with dependency of long rank (LDR) and dependency of short rank (SDR), to be able to make a more opportune and efficient control in form integrated at different levels from the functional hierarchy of the network. This time series modeling is based on measures taken from events with a periodic base. The objective of this research is to demostrate that the time series are an excellent tool for modeling of data traffic on Wimax networks. This is possible through the Box-Jenkins methodology that is presented in this article. At the end of this investigation there is a traffic model through a series of time ARIMA with surprisingly small error.